2009
DOI: 10.1097/tp.0b013e31819609d9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Transplantation of Adipose Tissue- and Bone Marrow-Derived Mesenchymal Stem Cells in the Infarcted Heart

Abstract: Background Mesenchymal stem cells hold promise for cardiovascular regenerative therapy. Derivation of these cells from the adipose tissue might be easier compared to bone marrow. However, the in vivo fate and function of adipose stromal cells (ASC) in the infarcted heart has never been compared directly to bone marrow derived mesenchymal cells (MSC). Methods ASC and MSC were isolated from transgenic FVB mice with β-actin promoter driving firefly luciferase and green fluorescent protein (Fluc-GFP) double fusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
77
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(87 citation statements)
references
References 43 publications
7
77
2
1
Order By: Relevance
“…cFB injection blocked electrical impulse propagation whereas nCMs improved or maintained the electrical function of the EHT. In vivo studies have similarly reported that while fetal CMs improved cardiac function (17), noncontractile cells such as fibroblasts, or mesenchymal stem cells did not (18). As a next step, we asked whether ESC-CMs, which have been shown to exhibit some but not all of the properties of nCMs (19), would appropriately integrate into the EHT.…”
Section: Resultsmentioning
confidence: 99%
“…cFB injection blocked electrical impulse propagation whereas nCMs improved or maintained the electrical function of the EHT. In vivo studies have similarly reported that while fetal CMs improved cardiac function (17), noncontractile cells such as fibroblasts, or mesenchymal stem cells did not (18). As a next step, we asked whether ESC-CMs, which have been shown to exhibit some but not all of the properties of nCMs (19), would appropriately integrate into the EHT.…”
Section: Resultsmentioning
confidence: 99%
“…Matrix-associated stem cell implants (MASIs) have a high potential for bone and cartilage regeneration (3,4). However, a major challenge of current approaches is death of the transplanted cells because of failed engraftment and/ or immune rejection (5,6). In case of graft failure, the transplanted cells die first (eg, because of hypoxia or mechanical factors), which leads to secondary macrophage influx and clearance of dead cells (7).…”
Section: Contrast Agentmentioning
confidence: 99%
“…Although MSCs have positive effects via production of growth factors favoring angiogenesis, 1 increase of antiapoptotic molecules, and suppression of inflammation, 2 these positive effects occur in the short timeframe between implantation and death of MSCs. 3 The loss in the implanted MSC numbers has been reported for implantation of several tissues using different implantation methods, including injection into the inflammatory bowel 4 and the infarcted hearts, 5,6 or implantation into the injured bone 7 and the ischemic kidney. 8 The disappearance of MSCs is closely associated with death-inducing conditions such as increased reactive oxygen species, 9 hypoxia, 10 and nutrient deprivation 11 in the wound environment along with nonspecific inflammation generated in response to implantation of any foreign material into the body.…”
Section: Introductionmentioning
confidence: 99%